Sexual Abuse of Street Children in Pakistan: Legal Protection Under International and National Law - Ullah, Nazir; Aziz, Saidatul Nadia Abd; Awal, Noor Aziah Mohd (Faculty of Law, Universitas Padjadjaran, 2024)
This study covers the social and legal dimensions of sexual abuse encountered by street children in Pakistan. It aims to elucidate the underlying reasons and contributory factors to child sexual abuse within the nation. This study employed qualitative methods, which involved analyzing data from primary sources such as acts of parliament and relevant journal articles. It highlights the exploitation of street children through prostitution, pornography, trafficking, and sex tourism. Therefore, it explored various manifestations of child sexual abuse both within street settings and beyond, alongside their foundational causes in Pakistani society. The study addresses the issue of sexual abuse among street children from two perspectives. Initially, it examines the different forms, prevalence, causes, and consequences of such abuse. Subsequently, it assesses the efficacy of both international and national laws and policies designed to counteract child sexual abuse. Despite the existence of legal frameworks in Pakistan aimed at addressing this issue, they are critiqued for being inadequate and inconsistent. The paper advocates for the introduction of more stringent legislation and enhanced trial transparency as measures to curb the incidence of child sexual abuse effectively. Updating and reinforcing existing legal provisions could significantly reduce the prevalence of such abuse in society.DOI: https://doi.org/10.22304/pjih.v11n1.a4